Synthesis of V-doped urchin-like NiCo2O4 with rich oxygen vacancies for electrocatalytic oxygen evolution reactions. (20th February 2022) - Wang, Xingzhao; Zhou, Yan; Luo, Jiabing; Sun, Fengchao; Zhang, Jun
Abstract: In this paper, 3D urchin-like V-doped NiCo2 O4 was synthesized as an efficient electrocatalyst for electrocatalytic oxygen evolution reaction (OER). NH4 VO3 and VCl3 act as various dopants to provide V 5+ and V 3+ ions, and the valence effects of V dopants on the structural modulation of NiCo2 O4 are examined systematically. XPS results show that the doping of V 3+ to NiCo2 O4 provides an extra 16.40% percentage of oxygen vacancies (Ov) than that of V 5+ doping, which can significantly modulate the OH − adsorption on NiCo2 O4 . EPR tests further confirm that the content of Ov in V 3+ doped NiCo2 O4 (V(Ⅲ)-NiCo2 O4 ) is 2.81 times higher than that in V 5+ doped NiCo2 O4 (V(V)-NiCo2 O4 ). Besides, V(Ⅲ)-NiCo2 O4 shows higher molar content of Co 2+ comparing to V(V)-NiCo2 O4, resulting in an increased probability of forming CoOOH catalytic active sites. Electrochemical investigations show that V(Ⅲ)-NiCo2 O4 electrocatalyst achieves excellent OER catalytic activity with a low overpotential of 344 mV at 10 mA cm −2, and it holds superior OER stability of electrocatalysis at 100 mA cm −2 for 50 h without significant change in electrode potential. Thus, this paper shows the importance of the valence of dopant precursor to the doped structures, and these findings pave a new sight of designing heteroatom doped electrocatalysts for OER. Abstract : Image, graphical abstract .